Biodegradasi Hidrokarbon Crude Oil di Kawasan PT. Bumi Siak Pusako-Pertamina Hulu menggunakan Konsorsium Bakteri Indigen - Riryn Novianty; Yuharmen Yuharmen (LPPM Universitas Muhammadiyah Riau, 2023)
Riau Province is one of the largest producing areas of crude oil. Drilling and refining petroleum often produce waste crude oil in large quantities. One method that can be used to degrade waste is biodegradation using a consortium of microorganisms. This study examined the effectiveness of a consortium of indigenous bacteria in degrading hydrocarbon compounds. Growth tests and the ability of isolates to degrade hydrocarbons were carried out by inoculating isolates in liquid Bushnell Haas media containing crude oil of about 5% and incubating for 16 days. The potency of the indigen bacterial consortium during the degradation process is influenced by several parameters, including pH, OD (Optical Density), dan CO2 observed on days 0, 4, 8, 12 and 16 days of incubation. KB4 is the superior consortium in degrading hydrocarbon crude oil. Based on the analysis using GC-MS instruments, the bacteria consortium can degrade two hydrocarbon compounds in crude oil.